Investigation of Mechanical, Tribological, and Electrical Properties of Silk Reinforced Polymeric Composite - Chikesh Ranjan; Gautam Sarkhel; Kaushik Kumar (Advances in Materials Science and Engineering)
The continuous demand of today’s scenario and ecological consciousness has made the researchers think about the utilization of alternate sources of materials without compromising the mechanical behavior and characteristics while focusing on the fulfillment of the desired requirements in the wide range of industrial applications. The present work is a noble attempt and a step towards the development of silk fibre composites (SFCs) reinforced with the vinyl ester matrix material. The processing and fabrication of SFRCs have been carried out using the traditional hand layup technique using untreated silk fibres (SFs) and silk cloths (SCs) in the form of single, double, and triple layers of SFs and SCs laminates oriented in uniaxial and biaxial directions. For the prepared composite samples, the density and void contents in the sample, mechanical characteristics in terms of their tensile and flexural strength, and tribological characteristics as well as the electrical impedance have been investigated. The percentage void content was found to be within the acceptance limit. The tensile and flexural test results show a considerable increment which indicates proper stress transfer from matrix phase to fibre with triple-layer cloths showing the highest tensile and flexural properties. In the tribological test, the coefficient of friction is higher in the case of cloth loading as fibre concentration increases significantly. In the impedance test, almost for all samples, the trend of change in conductivity with applied frequency is the same. From the economic perspective, the proposed composite is suitable for a wide range of applications in industries as well as this can be utilized as an alternate source of traditionally used floor tiles currently using ceramic materials. Also, the proposed composite has a biodegradable characteristic that is completely in accordance with the demand and consciousness involved in environmental and ecological perspectives.